Monster haircut! read with ladybird book 13 - Birkinshaw, Marie; Jackson, Shirley Nicholls, Judith (Ladybird London, 2001)
Welcome to the maddest salon in town, where every day is a bad hair day! This text is part of a series of books that are suitable for children who are early stages of learning to read.